Current perspectives on job-stress recovery - Sonnentag, Sabine, 1961-; Perrewe, Pamela L.; Ganster, Daniel C. (Emerald, 2009)
For decades, researchers have examined the job stressors and their outcomes for individuals and organizations. However, until now we know only little about the processes that reduce and reverse the effects of the stress process. This volume aims at filling this gap in the literature by focusing on processes related to recovery and unwinding from job stress. The book integrates various perspectives on the topic. The chapters demonstrate that recovery research is a very promising approach for understanding the processes of job stress and relieve from job stress more fully. Moreover, the chapters illustrate that recovery is a very important topic for practical job-stress interventions that have the potential to reduce the negative impact of job stress for employee health and well-being.
Keywords: Job stress.; elektronické knihy; electronic books